INCIDENCE OF FREE ZONES ON THE TAX IMPACT OF PARAGUAY - Arnaldo Sanabria, Diego; Magali Meza Fariña, Gabriela; Diana Mereles Lezcano, Ruth (Revista Gênero e Interdisciplinaridade, 2023)
The research work presents a study on the determination of the tax impact of Free Zones in Paraguay, since in recent years this system has been successful as a mechanism for attracting foreign direct investment, promoting an expansion of the industry. For this, a mixed approach methodology was used, the level of the investigation is descriptive, for which it was obtained as a result that the majority of the respondents are within the system of Free Zones from 6 to 10 years and that they opted for said system for economic benefits that it provides, it was also detected that the directors of the companies know in detail the declared taxes and this shows us that they have a good management of the information.